2022
DOI: 10.1155/2022/3817097
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Biomechanical Analysis of the Impact of Different Configurations of Pedicle-Screw-Based Fixation in Thoracolumbar Compression Fracture

Abstract: The aim of this experimental study was to analyze the impact of applying different configurations of the transpedicular fixation system on selected mechanical parameters of the thoracolumbar spine under conditions of its instability (after simulated fracture). Five study groups were tested: physiological, with compression fracture of the vertebra, with two-segment fixation, with three-segment fixation, and with four-segment fixation. Each of the analyzed study groups was subjected to axial compression, flexion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…It was observed that a PFS design with a short-segment configuration does not offer sufficient stability, particularly during flexion-extension movements. Such a PFS design may lack the necessary rigidity, resulting in an excessive range of motion at the thoracolumbar junction [1]. In line with these findings, McDonnell et al [2] and Bolesta et al [3] reported immediate stabilization of the affected segment when implementing LSF, along with achieving higher stiffness values compared to those seen in physiological systems.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…It was observed that a PFS design with a short-segment configuration does not offer sufficient stability, particularly during flexion-extension movements. Such a PFS design may lack the necessary rigidity, resulting in an excessive range of motion at the thoracolumbar junction [1]. In line with these findings, McDonnell et al [2] and Bolesta et al [3] reported immediate stabilization of the affected segment when implementing LSF, along with achieving higher stiffness values compared to those seen in physiological systems.…”
Section: Introductionmentioning
confidence: 83%
“…The experimental tests were conducted in a manner similar to the test procedure presented in a previous study that analyzed the impact of the length of fixated segments on the damaged thoracolumbar spine [1]. Loading was performed using an MTS 858 Mini Bionix testing machine (MTS Systems, Eden Prairie, MN, USA), and the specimens were subjected to forces simulating typical activities of daily life.…”
Section: Experimental Studymentioning
confidence: 99%
See 1 more Smart Citation
“…[58] The pedicle screw fracture observed in the clinic is mostly concentrated near the lowest nail tail cap. [59] Therefore, to reduce the risk of internal fixation failure, we can try to take a variety of methods: on the one hand, fusion is necessary. After fusion, the internal fixation stress can be reduced, and the possibility of fatigue fracture caused by long-term nonfusion fretting can also be reduced to a certain extent.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical management of thoracolumbar burst fractures is to correct kyphosis and provide adequate biomechanical stability for early mobilization while reducing surgical invasiveness and associated complications [6]. Biomechanically, having two or more xation levels above and below the fracture is a better option for thoracolumbar burst fractures, providing greater mechanical stiffness and reducing the likelihood of segment collapse and implant failure [7]. However, in addition to the interruption of spinal motion segments, long-stage immobilization was associated with more severe surgical invasiveness [8].…”
Section: Discussionmentioning
confidence: 99%